2002
DOI: 10.1002/mrm.10120
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Z‐spectroscopic imaging of cross‐relaxation parameters in tissues for human MRI: Theory and clinical applications

Abstract: A new method of pulsed Z-spectroscopic imaging is proposed for in vivo visualization and quantification of the parameters describing cross-relaxation between protons with liquid-like and solid-like relaxation properties in tissues. The method is based on analysis of the magnetization transfer (MT) effect as a function of the offset frequency and amplitude of a pulsed off-resonance saturation incorporated in a spoiled gradientecho MRI pulse sequence. The theoretical concept of the method relies on an approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
316
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(344 citation statements)
references
References 25 publications
25
316
3
Order By: Relevance
“…4) that are comparable to those commonly found at the same power level and about half the frequency offset at 1.5T (WM ϭ 0.40 -0.50, GM ϭ 0.30 -0.45) (1-4,10). To the best of our knowledge, this benefit of T 1 prolongation at high field strengths has not been previously reported.One point of caution in this study is that the T 1 of solid-phase protons has not been accurately reported for CNS tissue (1,2,4,12). However, simulations (1,2,4,12) have shown that MTR is little affected by slight variations in this parameter because the saturation transfer process is dominated by the water proton T 1 .…”
mentioning
confidence: 86%
“…4) that are comparable to those commonly found at the same power level and about half the frequency offset at 1.5T (WM ϭ 0.40 -0.50, GM ϭ 0.30 -0.45) (1-4,10). To the best of our knowledge, this benefit of T 1 prolongation at high field strengths has not been previously reported.One point of caution in this study is that the T 1 of solid-phase protons has not been accurately reported for CNS tissue (1,2,4,12). However, simulations (1,2,4,12) have shown that MTR is little affected by slight variations in this parameter because the saturation transfer process is dominated by the water proton T 1 .…”
mentioning
confidence: 86%
“…The MT ratio is a semiquantitative index that presents a limited view of the MT effect. More detailed analysis of pulsed, off-resonance MT data using the two-pool model of tissue (6,7) has been extended to in vivo imaging, in particular in human WM (8)(9)(10). The resulting method, termed quantitative MT imaging (QMTI), allows mapping of the parameters of the two-pool (liquid and semisolid) model of tissue: the ratio of semisolid to liquid protons F, the first-order forward and reverse exchange rate constants k f and k r (where k r ϭ k f /F), the spin-lattice relaxation rate R 1f of the free pool (R 1f ϭ 1/T 1f ), the spin-spin relaxation time constant of the free pool T 2f , and the "T 2 " of the restricted pool, T 2r (inversely related to the width of the restricted pool resonance).…”
mentioning
confidence: 99%
“…24 into Eq. 12, we obtain: [25] where g͑ d Ϫ ,T 2d ͒ represents the line-shape function (Lorentzian) and is commonly replaced with a gaussian or super-Lorentzian line-shape function to model the MT effect of macromolecule-bound water (30,31). In the current work, Eq.…”
Section: Appendixmentioning
confidence: 99%
“…The underlying mechanism of MT has been described successfully using a two-pool or three-pool model, including a pool of free protons and one or more pools of bound protons (27)(28)(29)(30)(31). To describe the MT effect in tissue, the line shape of the macromolecular component is best described using a super-Lorentzian or gaussian line shape in the Bloch equations rather than a Lorentzian line shape (29)(30)(31).…”
mentioning
confidence: 99%
See 1 more Smart Citation